A Transnosographic Self-Assessment of Social Cognitive Impairments (ACSO): First Data - Graux, Jérôme; Thillay, Alix; Morlec, Vivien; Sarron, Pierre-Yves; Roux, Sylvie; Gaudelus, Baptiste; Prost, Zelda; Brénugat-Herné, Lindsay; Amado, Isabelle; Morel-Kohlmeyer, Shasha; Houy-Durand, Emmanuelle; Franck, Nicolas; et al. (Frontiers in Psychiatry, 2019)
Social cognition refers to the mental operations underlying social interactions. Given the major role of social cognitive deficits in the disability associated with severe psychiatric disorders, they therefore constitute a crucial therapeutic target. However, no easily understandable, transnosographic self-assessment scale evaluating the perceived difficulties is available. This study aimed to analyze the psychometric qualities of a new self-administered questionnaire (ACSo) assessing subjective complaints in different domains of social cognition from 89 patients with schizophrenia, schizoaffective disorders, bipolar disorders or autism. The results revealed satisfactory internal validity and test-retest allowing the computation of a total score along with 4 sub scores (attributional biases, social perception and knowledge, emotional perception and theory of mind). Moreover, the ACSo total score was found correlated with other subjective assessments traditionally used in cognitive remediation practice but not with objective neuropsychological assessments of social cognition. In sum, the ACSo is of interest to complete the objective evaluation of social cognition processes with a subjective assessment adapted to people with serious mental illness or autism spectrum disorder.